Synthesis of functional polymer particles by dispersion polymerization in organic media: A tool toward stable electrophoretic inks. Issue 21 (7th August 2013) - Charbonnier, Antoine; Brochon, Cyril; Cloutet, Eric; Navarro, Christophe; Hadziioannou, Georges
ABSTRACT In this article, a simple route to obtain particles in one step from functional ionizable monomers in organic media by the use of acrylate‐based macroinitiator synthesized by nitroxide‐mediated radical polymerization is presented. Different positively ionizable monomers like 4‐vinylpyridine, (dimethylamino)ethyl methacrylate, or negatively ionizable ones like methacrylic acid and acrylic acid were tested. Several parameters were studied to control the particles size, their stability in different organic media, and the possibility to crosslink them. Finally, well‐defined, depending of conditions, functional latexes in organic media were produced in a simple way. This synthetic process constitutes the first step to produce electrophoretic inks for display applications such as electronic paper. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 4608–4617